Research trend on strategic management accounting techniques in business: a bibliometric analysis approach / Linda Hetri Suriyanti, Noorul Azwin Md Nasir and Siti Afiqah Zainuddin - Linda Hetri Suriyanti; Md Nasir, Noorul Azwin; Zainuddin, Siti Afiqah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
This study examines trends, maps themes, and outlines the research trajectory of Strategic Management Accounting Techniques (SMAT). A bibliometric analysis was conducted to identify research trends related to SMAT. The researchers used data from the Scopus database covering the years 1991 to 2024. A total of 121 published documents were retrieved and then analyzed using VOSviewer software and spreadsheets. A significant surge of interest and attention to SMAT peaked in 2023. Bibliometric mapping shows that early research on SMAT focused primarily on conceptual frameworks and theoretical underpinnings. The analysis identified several key themes and topics that are frequently explored in the SMAT domain, such as the integration of strategic management with accounting practices. Over time, there has been a shift towards empirical studies examining the practical applications and benefits of SMAT in various organizational contexts. The scarcity of research on SMAT underscores the importance and novelty of conducting a bibliometric analysis on this subject. The insights gained from this study help fill the existing knowledge gap and provide a foundation for future research. By identifying key trends and thematic areas, this study provides a roadmap for researchers to explore aspects of SMAT. Further research can explore the role of SMAT in artificial intelligence and big data analytics.